UPAYA MENINGKATKAN HASIL BELAJAR MENGGUNAKAN MODEL TALKING STICK PADA MATA PELAJARAN PAI DI SMP - Susilawati, Susilawati (Universitas Tanjungpura, 2021)
Abstract This study aims to improve the learning value of class VII A students of SMP Negeri 4 Pontianak. This research was conducted in two cycles, each of which had planning, implementation, observation and reflection. Data anatysis techniques that guide data management use a percentage (%) with a constant size of 100. Learning values are obtained from students test score of formative tests in the evaluation activities of each cycle. The result of study in cycle I showed that the average of learning value of students was 76.8 dan in cycle II showed that the average of learneng value of students increased to 80.9. Keywords : Enhancement, Learning Value, PAI, Talking Stick Model,